The value of ESG in emerging markets: Evidence from Indonesia, Malaysia, and Singapore - Baroto, Yatmoko; Ulupui, IGKA; Gurendrawati, E (International Journal of Management and Sustainability, 2026)
This study addresses a critical gap in the corporate finance literature by empirically investigating the causal link between Environmental, Social, and Governance (ESG) performance and firm profitability, as measured by Return on Equity (ROE), within the heterogeneous economies of Indonesia, Malaysia, and Singapore. Going beyond simple correlation, we advance the discourse by examining a theoretically salient moderating variable: firm size, a relationship that has received limited attention, particularly in the under-researched Southeast Asian context. Utilizing a comprehensive panel dataset of 1,420 publicly listed companies from 2012 to 2023, we employ sophisticated econometric methodologies, including First-Difference GMM (FD-GMM) and System GMM (SYS-GMM), to mitigate endogeneity and dynamic panel bias. Our main findings, derived from the robust SYS-GMM model, reveal a positive and statistically significant effect of ESG scores on ROE across all three countries, providing strong empirical support for the "doing well by doing good" hypothesis. Crucially, our analysis yields a novel and counterintuitive finding: the moderating effect of firm size on the ESG-ROE relationship is statistically insignificant. This result challenges the prevailing notion that only larger, resource-rich firms can effectively translate ESG investments into financial gains. It suggests that the positive financial spillovers of ESG practices are universal and not contingent on a firm’s scale. The consistency of these findings was validated through a series of robustness checks. This research makes three key contributions: (1) it provides rigorous, methodologically advanced evidence from a globally underrepresented region; (2) it introduces new empirical insights on the non-conditional nature of the ESG-profitability nexus; and (3) it offers valuable implications for investors and policymakers, demonstrating that ESG can be a universal value driver, thereby strengthening the case for integrated sustainability strategies across diverse corporate landscapes.